APLIKASI POINT OF SALE DAN PERAMALAN STOK BARANG MENGGUNAKAN METODE DOUBLE EXPONENTIAL SMOOTHING DI KURNIA STUDIO PAMEKASAN - Eko Cahayadi; Abd Wahab Syahroni; Sandy Vikki Ariyanto (Insand Comtech : Information Science and Computer Technology Journal, 2021)
In the current era of globalization, information technology is increasing very rapidly, especially in sales marketing. The computer as an intermediary created to facilitate human work. Kurnia studio which is engaged in the sale of goods and services requires a lot of information software that supports and provides satisfying services for consumers. Until now all the relaxation in the studio has not been computerized, starting from recording the order to storing other data related to sales to reporting, so that it is possible during the process of recording errors in the calculation, the accuracy of the data made and delays in searching the data required. Another problem faced by Kurnia Studio is that it is difficult to determine the stock of goods. Determination of the right stock of goods is needed to be able to divide the capital allocation so that services and sales can run smoothly. For that we need a point of sale application that is useful in finding data and making studio financial reports to be more accurate and faster. with this technology a forecasting system is also used using the double exponentiation smoothing method to analyze the stocking of goods for the following month. The use of this method is based on the stock of goods in the studio studio which tends to go up or down.Keywords : Point of Sale,, Forecasting,Metode Double exponential smoothing